Evaluación de dos protocolos de inseminación artificial a tiempo fijo con dos inductores de ovulación en vacas - Mancero Valero, Bryan Elias (2024)
In an experiment carried out at the Technical University of Babahoyo, the effect of two hormonal treatments, Estradiol Benzoate (BE) and Estradiol Cypionate (CPE), on the induction of ovulation and pregnancy percentages in cows was evaluated, using a completely randomized design (D.C.A). 24 cows were selected, divided into two groups of 12 animals each. BE treatment included application of an intravaginal progesterone device (DIB), followed by administration of 2 ml of BE, prostaglandin, equine chorionic hormone, and artificial insemination with GnRh. CPE treatment was similar, but with the addition of 1 ml of CPE instead of BE. The results showed that, in the group treated with BE, the follicles reached an average diameter of 10.81 mm, while in the group treated with CPE, the average diameter was 11.48 mm. Although the CPE showed a larger follicular diameter and a higher pregnancy percentage (58% versus 42% in the BE), these differences were not statistically significant (p > 0.05). These findings highlight the need for additional studies with a larger sample size to confirm these trends and evaluate the effectiveness of hormonal treatments in various reproductive contexts.